Objective Measurement of Physical Activity with Accelerometers in Autism Spectrum Disorder - Muhammad Reyhan Faza Firdaus; Jajat; Widy Dewi Nuryanti (Universitas Negeri Semarang, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that can affect children's involvement in physical activity. Low physical activity and high sedentary behavior have the potential to negatively impact the health and fitness of children with ASD. This study aims to describe the level of activity patterns and sedentary behavior of children with ASD, measured objectively using an accelerometer.. Penelitian ini menggunakan observasional deskriptif dengan pendekatan potong lintang (cross-sectional). The subjects of this study were nine children with ASD aged 6-18 years who were recruited purposively at the YPAC Bandung Special School (SLB-D). Activity was measured using an accelerometer worn for seven consecutive days. The data were analyzed descriptively, including energy expenditure, Metabolic Equivalent of Task (METs) values, sedentary behavior (sedentary bouts and sedentary breaks), and daily step count. The results showed that the average energy expenditure was 997.54 kcal with an average METs value of 1.038, indicating a predominance of very light-intensity activities. Children with ASD spend most of their time being sedentary, with long periods of sedentary behavior. Although there are variations in the number of daily steps between individuals, the intensity of physical activity remains relatively low. The conclusion of this study shows that children with ASD have low physical activity and are dominated by sedentary behavior. These findings emphasize the importance of developing structured and inclusive physical activity programs to increase physical activity intensity and reduce sedentary time in children with ASD.